IMPLEMENTASI MANAJEMEN KURIKULUM DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH DI MTsN BINJAI - Azmi Batubara, Aprillia Nurul; Padang , Rismoninta; Tri Putri, Clara; Andriani, Sri (IKAMAS: Manajemen Pendidikan Islam, 2022)
The implementation of curriculum management in improving the quality of education is motivated by the development of increasingly sophisticated and globalized science and technology (IPTEK), so that it has an impact on almost all human life on earth today, including educational institutions. Educational institutions are required to be able to anticipate these changes by realizing quality education. In education management, curriculum management needs to be carried out by holding and applying the existing management principles so that the output produced is of quality. The purpose of this study was to determine how the implementation of curriculum management in improving the quality of education at MTsN Binjai. This research uses a qualitative approach with the type of case study research. Data collection is done by observation, interviews, and documentation. The results of the research at MTsN Binjai are: (1) curriculum planning in improving the quality of education at MTsN Binjai has been carried out collaboratively, meaning that by involving school personnel in all stages of curriculum planning; (2) the implementation of the curriculum in improving the quality of education at MTsN Binjai has been carried out in accordance with the general principles of curriculum development; (3) the evaluation of the curriculum in improving the quality of education at MTsN Binjai is carried out very well, as evidenced by the existence of a systematic effort in setting implementation standards.